2018
DOI: 10.1093/neuros/nyy190
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Clinical Outcomes Following Surgical Correction of Adult Spinal Deformity

Abstract: The predictive nomogram that we developed using these data can improve preoperative risk counseling and patient selection for deformity correction surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…In addition to complications and risk factors related to gender, Gulbrandsen et al ( 30 ) indicated that females reported slightly more pain and worse function than males at the time of surgery. Finally, Sharma et al also showed that in spine surgeries gender interacted with obesity at 1 year of follow-up: obese males with at higher odds of improvement when compared to nonobese males; among females, obesity did not affect the odds of improvement ( 58 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to complications and risk factors related to gender, Gulbrandsen et al ( 30 ) indicated that females reported slightly more pain and worse function than males at the time of surgery. Finally, Sharma et al also showed that in spine surgeries gender interacted with obesity at 1 year of follow-up: obese males with at higher odds of improvement when compared to nonobese males; among females, obesity did not affect the odds of improvement ( 58 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, there were substantial differences between the patient's series and those in the comparison groups. When degenerative diseases and deformities were considered and analyzed together it was also shown that gender interacted with obesity at 1 year of follow-up; obese males showed a higher odd of improvement when compared to nonobese males while among females, obesity did not affect the odds of improvement ( 58 ). Nevertheless, it should be noted that numerous studies present in the literature did not investigate and analyze spinal fusion outcomes dichotomizing by gender, thus it is difficult to establish a real conclusion and draw definitive results.…”
Section: Discussionmentioning
confidence: 99%
“…We included studies in patients undergoing cervical spine (n = 3), thoracolumbar spine (n = 2), and lumbar spine (n = 8) surgery [3••, 5••, 6••, [23][24][25][26][27][28][29][30][31][32]. These studies reported predictive models (n = total number of models) to estimate post-surgical patient-reported outcomes of the following: return to work (n = 3), pain (n = 9), physical functioning and disability (n = 5), quality of life (QOL) (n = 6), and psychosocial disposition (n = 2) reported in Table 4.…”
Section: Predicted Patient-reported Outcomes By Spine Regionmentioning
confidence: 99%
“…Patient data for these risk assessment tools was derived from EMR data, QOD registry, and Multi-center AOSpine CSM North America or International study-specific registries for patients undergoing elective cervical and lumbar surgeries [3••, 6••, 26••,30,31]. The predictive accuracy of these tools ranged from fair to good, with Sharma et al exhibiting the greatest predictive accuracy with a c-index value of 0.764[30].…”
mentioning
confidence: 99%
“…However, there is room for improvement. 7,8 Machine learning (ML) shows promise to improve clinical decision-making and patient outcomes. It is a collection of statistical techniques that uses large quantities of data to develop a model to determine nuanced patterns and predicting outcomes.…”
Section: Introductionmentioning
confidence: 99%